Mundo interior e expressão: a filosofia da psicologia de Ludwig Wittgenstein - Fatturi, Arturo (Universidade Federal de São Carlos, 2010)
This thesis analyzes the grammar of the psychological vocabulary with the idea that inner world (the subjectivity) and external world (the behavior) are connected by grammatical relations which must be clarified through a conceptual inquiry and not through empirical findings. To reach to the objective we analyzed the common point of view that we have of our inner world and traces the linkings between our affirmations about the inner world and how they acquire meaning from this common point of view. The following step was to analyze the conception of privacy that the common point of view attributes to the events of the inner world. After this we argue that the common conception does not could be a base for the construction of a philosophical explanation of the inner world. Therefore the objective of the common vision of our interior world is not to elaborate a scientific explanation. At the same time we conclude that our common conception of the psychological vocabulary is not a proto-theory that must be developed by the philosophical investigations. From this we open the way to present the philosophical point of view of Ludwig Wittgenstein about the psychological vocabulary. We explain this point of view to clarify our objective. Subsequently we presents the conception of language of Wittgenstein and we link his conception with the way for which he treated or understanding of the psychological vocabulary. With this explanation we show that when we are dealing with the affirmations of our inner world - our psychological vocabulary - we are not contending with a dichotomy between behaviorism and Cartesianism. Wittgenstein shows that we have another form to explain our language about the inner world. According to Wittgenstein's philosophy of the psychology our behavior is an expression of the inner world, that is, the inner if express world through the behavior despite if it does not reduce to the behavior. With such idea, Wittgenstein admits that the relation enters our affirmations on the interior world cannot be understood in isolated way of our behavior. At the same time, our behavior alone is not the criterion for understanding of the inner world, is necessary that the behavior be considered inside of a specific language game that is our use of our concepts of the psychological vocabulary.
The Philosophy of the Psychology of Ludwig Wittgenstein
Keywords: Mente; Filosofia analítica; Filosofia contemporânea; Filosofia austríaca; Linguagem - filosofia; Filosofia da Psicologia; Filosofia de Ludwig Wittgenstein; Mundo interior e expressão; Expressivismo; Philosophy of language; Philosophy of mind; Philosophy of Psychology; Ludwig Wittgenstein s Philosophy; Inner word; Expression; CIENCIAS HUMANAS::FILOSOFIA